2018
DOI: 10.3889/oamjms.2018.312
|View full text |Cite
|
Sign up to set email alerts
|

Serum Apelin and Obesity-Related Complications in Egyptian Children

Abstract: BACKGROUND:The rapidly increasing prevalence of childhood obesity became a major burden on health worldwide, giving an alarm to clinicians and researchers. Adipocytes act as an active endocrine organ by releasing plenty of bioactive mediators (adipokines) that play a major role in regulating metabolic processes. Apelin is a recently identified adipokine that is expressed in adipocytes.AIM:The current work aimed to uncover the relation between serum apelin and childhood obesity and its related complications as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
2
10
2
4
Order By: Relevance
“…However, some data reported in literature show that APLN level is increased in obese patients suggesting that BMI is positively correlated with APLN levels [120,121]. Moreover, some authors have suggested that in obese patients APLN expression is elevated in white adipose tissue and decreased in brown adipose tissue.…”
Section: Apelin/apj Axis: Biological Rolementioning
confidence: 99%
“…However, some data reported in literature show that APLN level is increased in obese patients suggesting that BMI is positively correlated with APLN levels [120,121]. Moreover, some authors have suggested that in obese patients APLN expression is elevated in white adipose tissue and decreased in brown adipose tissue.…”
Section: Apelin/apj Axis: Biological Rolementioning
confidence: 99%
“…Excessive weight gain leads to severe complications such as hypertension, diabetes, atherosclerosis, and hyperlipidemia, which have been defined as "metabolic syndrome." However, only half of the obese patients with BMI from 30 to 50 kg/m 2 had metabolic disorders [3].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, AT in obese individuals are the former site of progressive infiltration by pro-inflammatory immune cells, which, together with increased inflammatory adipokine secretion, induce adipocyte insulin resistance. IL-17 and IL10 cells are part of obese AT infiltrating cells and are likely to be promoted by adipose [3].…”
Section: Introductionmentioning
confidence: 99%
“…43 Obestatin suppresses appetite, thus lessen food and water consumption as well as body weight gain and movement of foods through the digestive system. 54,56,57 This suggests that deficiency and over secretion of the hormone may be associated with the two mentioned diseases.…”
Section: Obestatinmentioning
confidence: 99%